Gambaran Tingkat Pengetahuan Remaja Putri Tentang Gangguan Siklus Menstruasi Siswi Kelas XI SMK PGRI Karangmalang Kabupaten Sragen - Aprilica Manggalaning Murti - Akbid YAPPI Sragen (Indonesian Journal on Medical Science, 2016)
Abstract: Most women have a normal menstrual cycle, sometimes cycles occur less than 21 days nor more than 35 days called the menstrual cycle disorders. Oligomenorrhea occurrence in adolescents of 16.7%. Based on data from adolescent gynecology clinic visits at the hospital Dr. Naidoo Semarang show menstrual cycle disturbances of 22.52% include menstrual irregularities and amenorrhoea. The aim of this study was to determine the level of knowledge of young girls about menstrual cycle disorders class XI student of SMK PGRI Karangmalang Sragen. This study was a descriptive research method with cross sectional approach. The population of all class XI student of SMK PGRI Karangmalang Sragen 2011. simple random sampling technique obtained a sample of 42 students. Univariate analysis using frequency distribution. The level of knowledge of young girls about menstrual cycle disorders SMK PGRI Karangmalang Sragen in 2011 on 14 April 2011 of 42 respondents majority have a level of knowledge in the category enough, 36 respondents (85.71%). Conclusion: The level of knowledge of young girls about menstrual cycle disorders class XI student of SMK PGRI Karangmalang Sragen majority in the category enough.Keywords: Knowledge, menstrual cycle disorders Abstrak: Sebagian perempuan memiliki siklus haid tidak normal, terkadang siklus terjadi kurang dari 21 hari atau lebih dari 35 hari yang disebut gangguan siklus menstruasi. Terjadinya oligomenorea pada remaja sebesar 16,7%. Berdasarkan data kunjungan poliklinik ginekologi remaja di RS Dr. Karyadi Semarang menunjukkan gangguan siklus menstruasi sebesar 22,52% meliputi irregularitas haid dan amenorea. Tujuan penelitian ini adalah untuk mengetahui tingkat pengetahuan remaja putri tentang gangguan siklus menstruasi siswi kelas XI SMK PGRI Karangmalang Kabupaten Sragen. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan cross secsional. Populasi semua siswi kelas XI SMK PGRI Karangmalang Sragen tahun 2011. Teknik simple random sampling diperoleh sampel sejumlah 42 siswi. Analisis univariate menggunakan distribusi frekuensi. Tingkat pengetahuan remaja putri tentang gangguan siklus menstruasi SMK PGRI Karangmalang Kabupaten Sragen tahun 2011 pada tanggal 14 April 2011 dari 42 responden mayoritas memiliki tingkat pengetahuan dalam kategori cukup, 36 responden (85,71%). Simpulan: tingkat pengetahuan remaja putri tentang gangguan siklus menstruasi siswi kelas XI SMK PGRI Karangmalang Kabupaten Sragen mayoritas dalam kategori cukup.Kata Kunci       : Pengetahuan, gangguan siklus menstruasi